Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Terdaftar Di BEI Tahun 2016-2020 - Kiki Amelia Bancin; Hendra Harmain (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to determine the effect of good corporate governance on the financial performance of companies listed on the IDX in 2016-2020. The variables used in this study are the board of commissioners (X1), the board of directors (X2), the audit committee (X3), and financial performance (Y). The method used in this study is a quantitative method with a purposive sampling technique. The type of data collection is secondary data which is accessed on the IDX official website. The results obtained partially show that the board of commissioners has no significant effect on the company’s financial performance, the board of directors has a significant effect on the company’s financial performance, and the audit committee has no significant effect on the company’s financial performance. Meanwhile, the three variables are; the board of commissioners, the board of directors, and the audit committee simultaneously have a significant effect on the financial performance of companies listed on the IDX in 2016-2020.